THE SUPERIOR MANAGEMENT SYSTEM OF THE ARMED FORCES AND THE INSTITUTION OF COMMANDER-IN-CHIEF OF THE ARMED FORCES IN THE FIRST REPUBLIC OF ARMENIA - Sumbatyan, Anush (State and Law, 2023)
In the article, the author raises the issues of military-strategic management in the parliamentary system of the First Republic of Armenia comparing them with the regulation of such relations in other forms of government (presidential, semi-presidential, parliamentary and monarchic). The author concludes that in the modern Republic of Armenia, the military-strategic management system of the defense sector, which has a strict Govetnment and Prime Minister-centered feature which a vision of unusual regulation and threatens the defense interests of the country.